Distal Versus Proximal Radial Artery Access for Cardiac Catheterization: 30‐Day Outcomes of the DIPRA Study - Karim Al‐Azizi; Ghadi Moubarak; Chadi Dib; Sameh Sayfo; Molly Szerlip; Sibi Thomas; Julie McCracken; Adam Smith; Uma Kelavkar; Sarah Hale; Johanna Van Zyl; Shelby L. McCoy; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Proximal radial artery (pRA) access for cardiac catheterization is safe but can jeopardize subsequent use of the artery because of occlusion. Distal radial artery (dRA) access in the anatomical snuffbox preserves the radial artery, but safety and potential detrimental effects on hand function are unknown. Methods and Results In the DIPRA (Distal Versus Proximal Radial Artery Access for Cardiac Catheterization and Intervention) study, a single‐center trial, 300 patients were randomized 1:1 to cardiac catheterization through dRA or pRA. The primary end point of change in hand function from baseline to 30 days was a composite of the QuickDASH (Quick Disabilities of the Arm, Shoulder and Hand) questionnaire, hand‐grip test, and thumb forefinger pinch test. Secondary end points included access feasibility and complications; 254 of 300 patients completed follow‐up at 30 days; of these, 128 were randomized to dRA and 126 to pRA with balanced demographic and procedural characteristics. Both groups had similar rates of access site bleeding (dRA 0% versus pRA 1.4%; P=0.25). Six patients with dRA failed access compared with 2 patients with pRA. Radial artery occlusion occurred in 2 pRA versus none in dRA. There were no significant differences in change in hand function, median hand‐grip (dRA 0 [−3.2, 3.3] versus pRA 0.7 [−2.3, 3.3] kg; P=0.21), pinch‐grip (dRA −0.3 [−1.2, 0.5] versus pRA 0 [−0.9, 0.9] kg; P=0.09), and QuickDASH (dRA 0 [−4.6, 2.3] versus pRA 0 [−4.6, 2.3] points, P=0.96). There was no significant difference in the composite of hand function between pRA and dRA. Conclusions dRA is a safe strategy for cardiac catheterization with a low complication rate. Compared with pRA, there is no increased risk of hand dysfunction at 30 days. Registration URL: https://www.ClinicalTrials.gov. Unique identifier: NCT04318990.